2018
DOI: 10.1103/physreve.98.052124
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase transition in quantum-heat-engine cycles

Abstract: We explore signatures of a topological phase transition (TPT) in the work and efficiency of a quantum heat engine, which uses a single layer topological insulator, stanene, in an external electric field as a working substance. The magnitude of the electric field controls the trivial and topological insulator phases of the stanene. The effect of TPT is investigated in two types of thermodynamic cycles, with and without adiabatic stages. We examine a quantum Otto cycle for the adiabatic and an idealized Stirling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…Accordingly, many proposals to realize them can be found in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], some of which take into account finite-time engine cycles [22][23][24][25][26]. In addition, the effects of the profound quantum nature of the QHE such as such as cooperativity [27][28][29][30][31], coherence and correlations [32][33][34] on the performance of QHEs have also been investigated. Following the demonstration of a singleion engine cycle [35], genuine QHE experiments have been reported [36] with a single spin in a nuclear magnetic resonance (NMR) set up [36,37], a cold Rb atom [38], and an nitrogen-vacancy (NV) center in diamond [39].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many proposals to realize them can be found in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], some of which take into account finite-time engine cycles [22][23][24][25][26]. In addition, the effects of the profound quantum nature of the QHE such as such as cooperativity [27][28][29][30][31], coherence and correlations [32][33][34] on the performance of QHEs have also been investigated. Following the demonstration of a singleion engine cycle [35], genuine QHE experiments have been reported [36] with a single spin in a nuclear magnetic resonance (NMR) set up [36,37], a cold Rb atom [38], and an nitrogen-vacancy (NV) center in diamond [39].…”
Section: Introductionmentioning
confidence: 99%
“…It was clearly observed that cells quite well penetrated into the inner walls of pores and the surface of the scaffolds by forming layers between the spherical structures of the nanocomposite films. Higher roughness as nanospherical structures of the film may have a critical role on improving the attachment and spreading of the cells . Spherical structures of PC8A2%0.4ZnO nanocomposite film and nesting fibroblasts between these structures were seen clearly in the SEM micrograph of the PC8A2%0.4ZnO.…”
Section: Resultsmentioning
confidence: 97%
“…Other potential impact of quantum fuels can be envisioned in the fields of quantum batteries [204,205], and thermal quantum annealing [205][206][207] or error correction [115]. Besides, it can be a promising direction to explore quantum fuels for topological quantum heat engines [208,209]. Optimization of quantum thermodynamical processes and quantum thermal machines, in general, can benefit from quantum machine learning methods [210].…”
Section: Discussionmentioning
confidence: 99%